2015
DOI: 10.1007/s00044-015-1412-y
|View full text |Cite
|
Sign up to set email alerts
|

Quinoid systems in chemistry and pharmacology

Abstract: In this paper, we present a brief review of quinoid systems, focusing on their chemical synthesis over the last decade. We address not only major methods of synthesizing quinoids, but also their involvement in biological processes. We highlight their medical relevance and versatility, including antitumor, antiretroviral, or antihypertensive agents, properties determined by their various patterns of substitution. Graphical AbstractKeywords Quinone Á Synthesis Á Cytotoxicity Á Natural products Á Pharmacology Á R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 90 publications
0
11
0
2
Order By: Relevance
“…Naphthoquinones (naphthalenediones) form an important part of some pharmacophores in medicinal chemistry (Ló pez et al, 2015). During an exploration of antimalarial drugs, Fieser (Fieser & Fieser, 1935) indicated that aminoiminonaphthoquinones, although difficult to form, had interesting medicinal properties.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Naphthoquinones (naphthalenediones) form an important part of some pharmacophores in medicinal chemistry (Ló pez et al, 2015). During an exploration of antimalarial drugs, Fieser (Fieser & Fieser, 1935) indicated that aminoiminonaphthoquinones, although difficult to form, had interesting medicinal properties.…”
Section: Chemical Contextmentioning
confidence: 99%
“…Naphthoquinone is a quinone-based, highly redox-active compound that can redox cycle with its semiquinone radical 14 . Quinone-based compounds may have one or more of the following functions: electron transport chain inhibition, oxidative phosphorylation uncoupling, DNA intercalation, reductive alkylation, and free radical generation 15 . Thus, naphthoquinone inhibits photosynthesis by disturbing photosynthetic electron transport in plants 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%
“…Quinoidal molecules have received particular attention from chemists, physicists and biochemists as building block in the fields of dyes chemistry, conducting organic materials, supramolecular chemistry and pharmacology [1][2][3][4][5][6]. Over the last three decades, they have also been strongly investigated as ligand, for the design of complexes that could be used in a wide range of applications ranging from catalysis and molecular electronics, to magnetism or optics [7][8][9][10].…”
Section: Introduction and Scopementioning
confidence: 99%